Respostas

2014-04-25T14:34:41-03:00
Vamos lá:

a) f(x) = x² + x + 2
a = 1; b = 1 e c = 2

b) f(x) = - 4x² - 2,5
a = - 4; b = 0 e c = - 2,5

c) f(x) =  \frac{x^2}{3}- \frac{2}7}x
a = 1/3; b = -2/7 e c = 0

d) f(x) = 3x - 1 - 9x²
a = - 9; b = 3 e c = - 1

e) f(x) = (1 + x²)7,6
f(x) = 7,6 + 7,6x²
a = 7,6; b = 0 e c = 7,6

f) f(x) = 2x(- x - 5/x + 6)
f(x) = -2x² - 10 + 12x
a = - 2; b = 12 e c = - 10

Espero ter ajudado.

2014-04-25T14:35:47-03:00
Coeficiente é o numero antes dos termos A, B e C
a) A= 1 B= 1 C= 2
b) A= -4 B= 0 C= 2,5
c) A=  \frac{1}{3} B= - \frac{2}{7} C= 0
d) A= -9 B= 3 C= -1
e) A= 7,6 B= 0 C= 7,6
f) A= -2 B= 12 C= -10

espero ter ajudado...